Effect of vibration therapy on upper limb range of motion and muscle strength in children with hemiplegia: a randomized controlled trial - Walaa E. Heneidy; Mahmoud Adel Farouk; Khaled A. Olama; Amira F. Ibrahim (Bulletin of Faculty of Physical Therapy, 2025)
Abstract Background Children with hemiplegic cerebral palsy (HCP) suffer from muscle weakness and restricted joint flexibility in the involved upper limb. This affects their performance in everyday tasks. Therefore, the current study aimed to investigate the effect of vibration therapy (VT) on upper limb range of motion (ROM) and muscle strength in these children. Methods The study included 30 children from both sexes aged 3 to 6 years who were diagnosed with HCP. Subjects were recruited from the outpatient clinic, Department of Physical Therapy, Qanater Central Hospital, Qalyubia, Egypt. Participants were randomly assigned to control group A (n = 15) and participated in the designed physical therapy programme for 1 h, while study group B (n = 15) completed the same programme for 30 min in addition to VT administered via whole-body vibration (WBV) device on upper limb for another 30 min, three sessions/week for four successive weeks. The upper limb ROM was assessed by the digital goniometer and muscle strength by Lafayette handheld dynamometer. Statistical SPSS package program version 25 for Windows (SPSS, Inc., Chicago, IL, USA) was used, paired t-test was applied to investigate within-group changes, and unpaired t-test was used to compare the study group and control at pre- and post-treatment. Results The children in the study group achieved superior improvements in ROM of shoulder abduction (8.25%), forearm supination (35.76%), wrist flexion (34.62%), and wrist extension (14.03%) compared to the control group. They also had improved muscle strength of shoulder abductors (53.94%), wrist flexors (47.06%), and wrist extensors (40.24%) at post-treatment compared to baseline than children in the control group. Conclusions Combining VT using the WBV device with the PT programme showed higher percentages of improvements in the ROM for shoulder abduction, forearm supination, and wrist flexion and extension, as well as muscle strength in shoulder abductors and wrist flexors and extensors, in children with HCP compared to the PT programme alone indicating the clinical benefit of integrating the WBV within PT programme in rehabilitation of these children. Trial registration Effect of whole-body vibration on upper limb range of motion and strength in children with hemiparetic cerebral palsy, ID NCT05896111 . Registered 7 June 2023 — retrospectively registered.